The Options And Design Improvements Of The Electric Grid Of Sarawak As An Example For Developing Countries - Prashobh, Karunakaran (Global Journal Of Engineering Science And Researches, 2015)
This research is a reference for decision makers of electric grids especially in developing countries. This is done by describing the 90 year old Sarawak electric grid, including design improvements to further enhance it. The grid includes the power plants, the substations and the transmission and distribution lines. Grid equipment (notably power stations) is so expensive that only politicians of the highest level can make decisions regarding them. The problem is only a few engineers are in politics. Therefore there is a need for an easily accessible scholarly paper on the power system options for developing countries.